Integration of Islamic perspective into the global perspectives textbook of an International school in Qatar - Alam, Mohd Abdul (Kulliyyah of Education, International Islamic University Malaysia, 2021)
The purpose of this qualitative case study was threefold. The first phase of this research explored to what extent standard Global Perspectives (previously known as Social Studies) textbook and hereto referred as “GP” contributed to six grade 8 students and one GP teacher's understanding of Islamic Perspective in the GP subject from the 'The Next Generation School', hereto referred as “TNG” in Wakra, Qatar. The second phase of this research drafted and proposed an integration model that was used to integrate Islamic Perspective into two chapters from the GP textbook. The third and final phase of this study explored to what extent the Islamised GP textbook contributed to the same set of participants' understanding of Islamic Perspective in the GP Subject. The key findings are that participants were unable to understand Islamic Perspective in the GP Subject when standard GP textbook was used while the use of Islamised GP textbook has contributed to their understanding of Islamic Perspective in the subject. This demonstrates that the proposed integration model has contributed to the integration of Islamic Perspective into the GP textbook. Thus, the main contribution of this thesis is the development of a proposed integration model to integrate Islamic Perspective into standard GP textbook and confirm previous studies that stated Islamised learning materials will help to contribute in students and teachers' understanding of Islamic Perspective in a given subject. In order to explore to what extent standard GP textbook contributed to the participants' understanding of Islamic Perspective in the GP subject, a qualitative case study approach was deployed. Informal Document Analysis of current standard GP textbook for grade 8 and supplementary notes was conducted while two classroom observations of Grade 8 GP classes were conducted. This was followed by semi structured interviews with TNG Principal, two GP teachers, two Islamic Studies hereto referred as “IS” teachers and six Grade 8 students. Thereafter, the proposed integration model was used to integrate Islamic Perspective into two chapters from the GP textbook and train the GP teacher how to teach the two Islamised chapters in classes. Classroom observations and semi-structured interviews with same set of participants were conducted to explore to what extent the use of Islamised GP textbook contributed to the same set of participants' understanding of Islamic Perspective in the GP subject. Thematic Analysis was subscribed for analysing the data and three main themes emerged. The results have been promising as stated earlier. The positive results demonstrate that this proposed integration model can be used in schools wanting to teach Social Studies or Global Perspectives subject with Islamic Perspective. Further research is needed to explore if the proposed model can be used to integrate Islamic Perspective into other subjects' textbooks as well.